Reflexiones sobre las características constitutivas de la gestión integral (2009)
This article presents the form as is interpreted the concept of “ integral management “ in the context of the Mastery in Quality and Integral Management. We examine first the concept of “ the quality “, appearing an extended vision of the same one that exceeds the traditional relation between a client and its supplier. Later the internal configuration of an organization is analyzed from four elements differentiated but articulated: the structure of the business, the strategic management, organizational culture and management systems; the latter mentioned should be integrated based on the compatibility of its elements. But the integral management includes also external elements to the organization related, in the approach of this Mastery, to three components of the sustainable development: the economic growth, the protection of the environment and the social cohesion; so that the integral management must include the complex integration of the internal and external elements that enable the organizational sustainability.